Transpore Tape and Transparent Film Dressing on the Incidence of Early-Stage Phlebitis: A Comparative Randomized Trial - Thangkratok, Pramote; Pongpirul, Krit; Sriratanaban, Jiruth (Siriraj Medical Journal, 2025)
Objective: This study compares the effectiveness of transpore tape and transparent film dressing on the incidence of early-stage phlebitis among patients with peripheral venous catheters. Materials and Methods: We conducted a randomized controlled prospective study on 308 inpatients in the internal medicine wards of a community hospital in Thailand, from November 2020 to March 2021. The visual infusion phlebitis scale was employed for assessments by registered nurses at least every eight hours. Results: Demographic and health factors were similar in both transpore tape and transparent film dressing groups. Notably, early-stage phlebitis was detected in 77.92% of patients in the transpore tape group, significantly higher than the 66.88% in the transparent film group (p=0.030). The group using Transpore tape had a 1.16 times higher risk of early-stage phlebitis than the group using transparent film dressing (RR = 1.16, 95% CI = 0.116-0.452). Statistical analysis showed a significant difference in catheter removal time between the two groups. Conclusion: Transparent film dressings demonstrated greater efficacy in reducing early-stage phlebitis incidences in patients with peripheral venous catheters, suggesting their preferable use in clinical settings.